Peningkatan Kecerdasan Interpersonal Melalui Permainan Tradisional pada Anak Kelompok B - Widayati Widayati (Universitas Trunojoyo Madura, 2017)
This study aims to improve early childhood entrapersonal intelligence through traditional games. This reseach was do in TK Mardi Putra 03 Desa Sumber Brantas, Kota Batu-Malang. This research used actiob reseacrh. Data analysis used Kurt Lewin design. The result of the research shows was childrens’s intrapersonal intelligencesthrough traditional games could increasi of grade B oinderganten. The end of result of the overall analysis data was the precentage increase wich showed from pre-intervency class average is 38,9% up to 82,13% at posttest result.